Inovasi proses penjualan dan pembelian bahan rujukan terpakai (innovation of buying and selling process for used reference materials) / Zuraini Jusoh ...[et al.] - Jusoh, Zuraini; Zainal, Nur Amirah; Abu Bakar, Nurhidayah; Mohd Rahmatullah, Dina Adriana; Ab Rahman, Nur Zulaikha; Ahmad Zaifuddin, Farah Adibah; Noor Hamidy, Nurul Aqilah (Universiti Teknologi MARA, 2020)
Students need the used of reference materials because they want to save their money for daily expenses. It is also as their side income if they become as a seller. However, the available buying and selling process using Whatsapp as a medium seen inefficient because the user was faced with several problems. Among the problems were incomplete advertisements information, sale status cannot be updated automatically and the process of buying and selling takes too long. Therefore, the construction of the BOOKU webpage is recommended to solve the problems. There was a several methods used in problem selection phase such as brainstroming, preliminary study of problems, verification and validation as well as T-shape Matrix. Ishikawa diagram has been used to identify the cause and effect of the problem in terms of material, process, human and environmental factors. A review from user also was carried out to obtain an endorsement of the problem in hand. Then the SWOT analysis method was used to assess the suggestion solution. After the completion constuction of BOOKU webpage, a few trials were carried out to ensure the BOOKU webpage functioned properly. Again, a review from the user was carried out based on the trials results. The result showed majority of users was agreed on the BOOKU webpage as a good solution for identified problems. The BOOKU webpage can provide a completed advertisement, automatically updated the sale status and the buying and selling process has been shorten from seven days to one day. For the spin-off project, the BOOKU website is planned to be devoted to the borrowing service for used of reference materials. Meanwhile for the purpose of replicating, the BOOKU webpage can be adapted in the school level. In conclusion, the BOOKU webpage can increase the quality of available process. It also can optimize the use of manpower and time.